Public narratives under intensified market conditions: Chile as a critical case. Issue 1 (2nd January 2018) - Santori, Diego
ABSTRACT: This paper aims to extend existing theorisations around the notion of public narratives by analysing their regulatory effects under intensified market conditions. My analysis suggests that public narratives constitute a liminal space, one that it is not exclusively real or imaginary, factual or normative, but that simultaneously affects and is affected by vernacular practices and wider discursive structures. However, this paper argues that, under extreme conditions, these public narratives become a rigidifying space with homogenising/normalising effects. To do this I look at a set of 'obligatory scenes' captured in tales of success and struggle of teachers, parents and students in popular newspapers and fringe media in Chile. These accounts share a common ground: national assessment as a framework of intelligibility for the practices of parents, teachers and students. The central claim of this paper is that under intensified market conditions the scenes captured in these publicly available stories become 'obligatory' storylines, and their protagonists idealised policy subjects.